Advanced coating technologies with spectral alteration for solar applications - Yalçın, Refet Ali. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Spectrally selective coatings are used to maximize the efficiency of solar thermal systems and they are designed based on the application. This study focuses on two solar applications; solar thermal energy systems and greenhouses. For solar thermal energy systems, the coating should have high absorptance at solar wavelengths and low emittance at the infrared wavelengths, where absorber emits heat to maximize the heat transfer to the working fluid. For greenhouse applications, coating should provide high radiation at the photosynthetic spectrum and distribute light uniformly and diffusely. This study focuses on fluorescent and non-fluorescent pigmented coatings that consist of a binder and well dispersed nanometer or micrometer sized particles that are known as pigments, selected to achieve the desired spectrally selective behavior based on application. Radiative behavior of coatings depends on coating thickness, pigment size, concentration, and the optical properties of the binder and pigment materials that can be identified by modeling the radiative transfer across these coatings. Models are developed for the problems considered to solve the radiative transfer equation based on the governing physics to predict the spectral reflectance, transmittance and light distributions in conjunction with Lorenz-Mie theory and T-matrix methods that are used for predicting radiative transfer properties. These models are used to design coatings to achieve optimal behavior for considered applications. It is found that the model used for designing pigmented coatings of solar thermal systems can be very critical, and coatings must be designed using a unified model considering the effective medium theory and four flux method together with Lorentz-Mie theory. Besides, it is found that while fluorescent coatings can improve spectral distribution of irradiation for photosynthetic production, they also lead to a significant decrease in the transmittance, decreasing the irradiance when used for traditional greenhouses. However, for vertical farms it is found that using fluorescent particles in coatings both improve distribution of light and effective PAR, resulting around 35% increase in yearly crop production for lettuce.
Keywords: Protective coatings; Spectral energy distribution.